Marketing Research Quantitative Analysis for Large Sample: Comparing of Lisrel, Tetrad, GSCA, Amos, SmartPLS, WarpPLS, and SPSS - Purwanto, Agus; Asbari, Masduki; Santoso, Teguh Iman; Haque, Marissa Grace (Jurnal Ilmiah Ilmu Administrasi Publik, 2019)
ABSTRACTThe purpose of this study is to compare the results of quantitative research data analysis in the marketing field using Lisrel, Tetrad, GSCA, SPSS, SmartPLS, WarpPLS and Amos software for a large sample, in this study the number of samples was 500 respondents. This research method is quantitative and research data analysis uses the four types of software to obtain a comparison of the results of the analysis. The analysis in this study focuses on the analysis of hypothesis testing and regression analysis. The data from this study uses quantitative data derived from questionnaire data totaling 500 respondents with three research variables, namely the independent variable digital marketing, customer satisfaction, and the dependent variable customer loyalty. Based on the results of the analysis using Lisrel, GSCA, SPSS, SmartPLS, WarpPLS and Amos software for a large sample of 500 respondents, the results showed that there was no significant difference in the significance value of p-value and t-value. There is also no significant difference in the determination value, and the correlation value in the resulting structural equation also has no significant difference in results.